The Concept of Mahdī in Shī'ī Theology - Nurul Fajri (Refleksi, 1999)
As Shī’ī eschatological doctrine, thus the concept of the Mahdi consists of the belief in the Imām Mahdī (divinely guided one) or the Hidden Imām who will reappear at the end of time as a savior realizing sociopolitical justice and equity through which a peaceful life based on the ideals of religious (Islamic) teaching may be realize an ideal religious society.